Pancreatic Cancer in 2014 - Kaltsas, Serafim; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
No abstract available. Image: Purple Crane (Folded by school children for pancreatic cancer patients). From Wikimedia Commons (Author: Erinleary). http://commons.wikimedia.org/wiki/File:Purple_Crane.jpg